3c*5a*2a+8=

Simple and best practice solution for 3c*5a*2a+8= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3c*5a*2a+8= equation:


Simplifying
3c * 5a * 2a + 8 = 0

Reorder the terms for easier multiplication:
3 * 5 * 2c * a * a + 8 = 0

Multiply 3 * 5
15 * 2c * a * a + 8 = 0

Multiply 15 * 2
30c * a * a + 8 = 0

Multiply c * a
30ac * a + 8 = 0

Multiply ac * a
30a2c + 8 = 0

Reorder the terms:
8 + 30a2c = 0

Solving
8 + 30a2c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 30a2c = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 30a2c = 0 + -8
30a2c = 0 + -8

Combine like terms: 0 + -8 = -8
30a2c = -8

Divide each side by '30c'.
a2 = -0.2666666667c-1

Simplifying
a2 = -0.2666666667c-1

Combine like terms: -0.2666666667c-1 + 0.2666666667c-1 = 0.0000000000
a2 + 0.2666666667c-1 = 0.0000000000

Factor out the Greatest Common Factor (GCF), 'c-1'.
c-1(a2c + 0.2666666667) = 0.0000000000

Subproblem 1

Set the factor 'c-1' equal to zero and attempt to solve: Simplifying c-1 = 0 Solving c-1 = 0 Move all terms containing a to the left, all other terms to the right. Add '-1c-1' to each side of the equation. c-1 + -1c-1 = 0 + -1c-1 Remove the zero: 0 = -1c-1 Simplifying 0 = -1c-1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(a2c + 0.2666666667)' equal to zero and attempt to solve: Simplifying a2c + 0.2666666667 = 0 Reorder the terms: 0.2666666667 + a2c = 0 Solving 0.2666666667 + a2c = 0 Move all terms containing a to the left, all other terms to the right. Add '-0.2666666667' to each side of the equation. 0.2666666667 + -0.2666666667 + a2c = 0 + -0.2666666667 Combine like terms: 0.2666666667 + -0.2666666667 = 0.0000000000 0.0000000000 + a2c = 0 + -0.2666666667 a2c = 0 + -0.2666666667 Combine like terms: 0 + -0.2666666667 = -0.2666666667 a2c = -0.2666666667 Divide each side by 'c'. a2 = -0.2666666667c-1 Simplifying a2 = -0.2666666667c-1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 6ab+-26b+13c+15ab+-24b= | | 15a+25b= | | 101+80+65+y=(4-2)180 | | 1-5n+1+3n= | | 101+80+75+y=(4-2)180 | | 9a+6ab+39c+6ab+-26b+13c= | | 10x-1=328 | | 15v-8v=28 | | 15v-18v=28 | | 74+89+98+y=(4-2)180 | | 13ab+-7b+17a+2ab+b= | | 3(4x+9)-6x=0 | | 42=2w+16 | | 3X=1-y-4z | | 2x+4x+6x+8x=360 | | 72+100+83+y=(4-2)180 | | 2ab+-17b+13ab+-7b= | | cos(5x)+cos(7x)=cosx | | 6+-2c+3=7+c | | y-1=-1(x+3) | | a-b=5b | | 3x-3=7x-1 | | 25x^2-45-10=0 | | 6x^7=11x^6 | | 13c+4ab-9b+2ab+-17b= | | 6+2c+3=7+c | | 13k^2+26k+13= | | X(x-2a)+a^2+1=0 | | w^6+8w^3+7=0 | | d^6+2d^3-80=0 | | 9a+26c+2ab+13c+4ab-9b= | | -14y=7x+1 |

Equations solver categories